Effectiveness of Implementing Tgt-Type Cooperative Model Assisted By Baamboozle Media on Student Learning Outcomes - Adelia Febryanti; Jufriadi (South Sulawesi Education Development, 2025)
This study aims to determine the effectiveness of implementing the Teams Games Tournament (TGT) cooperative model assisted by Baamboozle media on student learning outcomes in Islamic Religious Education and Character Education for eighth-grade students at SMPN 2 Lamasi. This research employs a quasi-experimental design with a pre-test/post-test nonequivalent control group design. The population comprises all eighth-grade students at SMPN 2 Lamasi in the 2024/2025 academic year. Purposive sampling was utilized, yielding 52 students divided into experimental (26 students) and control groups (26 students). Data collection employed validated instruments including pre-tests and post-tests, analyzed through descriptive and inferential statistics using SPSS. Results demonstrated significant improvement in the experimental group's post-test scores (mean: 85.77) compared to the control group (mean: 74.23), representing increases from pre-test scores of 57 and 56 respectively. The independent sample t-test revealed a significance value of 0.000 < 0.05, confirming H₀ rejection and H₁ acceptance. This indicates that the TGT cooperative model assisted by Baamboozle media is significantly more effective than conventional learning methods in enhancing Islamic Religious Education and Character Education learning outcomes.